Rehabilitation effect on psycho-emotional well-being in women with surgically treated vulvar cancer: a randomised controlled trial - Blinov V. Dmitry; Antonina G. Solopova; Elena V. Gameeva; Nazim G. Badalov; Vsevolod N. Galkin; Mikhail A. Eremushkin; Alexandra M. Stepanova; Alexander E. Ivanov; Olga S. Gridasova (Вестник восстановительной медицины, 2024)
Introduction. Surgical treatment of vulvar cancer (VC) entails mental and somatic disturbances due to pain, body image changes, and sexual dysfunction, which are closely associated with impaired social functioning and reduced overall quality of life. However, the results evaluating the impact of rehabilitation programmes on various components of quality of life in these patients remain limited.